Membangun Teologi dalam Prespektif Wesleyan-Arminian - Marthen Ballu (SANCTUM DOMINE: JURNAL TEOLOGI, 2015)
In the XVIII century, theology development was oriented to the conclusions that fulfilled human ratio demand. All super natural things that could not be measured by ratio would be disposed. All super natural forms in the bible were considered as myths and ancient society believe that they were no more relevant for modern society. Regarding to theology formulas relaid on human being ratio, John Wesley had come up with a genuine approach in developing theology. John Wesley used resources to develop his Theology that can be grouped as two parts: Scripture as a prime source and Church tradition, experiences, mind as a secondary source. Resources that John Wesley used are resources which are still relevant today to develop Wesleyan-Arminian Theology.